Religious Value in The Anthology of Poems 100 Pejalan (Study of Hermeunitics of Poems) - Suta Wardianto, Bayu (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Poetry is a beautiful, abstract, and meaning-filled strand of words based on the interpretation of the author and his readers. Of the various meanings of poetry, one of them is the meaning of religiosity or religious value contained in poetry. This research aims to examine and descript the religiosity contained in the anthology of poems 100 Walkers. The method in this study is qualitatively descriptive, with the technique of see and note which becomes a step of data collection. The research stage is carried out by collecting data, reducing data, and conducting data analysis to describe religious values in poetry collections. The results of the research found in this study are the existence of three types of religious values contained in the anthology of 100 Walker poems, including human religiosia with god, human religiosia with humans, and human religiosias with himself. From each religios or relationship, there are values such as piety, sincerity, fortitude, caring, mutual help, and inner feelings.